An engineering geomorphological characterisation of the 1963 vajont slide - Wolter, Andrea; Stead, Doug; Ward, Brent C.; Clague, John J. (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="{"1":2,"2":"The 1963 Vajont Slide is one of the most studied natural disasters in the world, with over 150 publications on its cause, mechanisms, behaviour, and effects. Most of these studies have considered the event from a descriptive, engineering geology, structural geology, or geophysical perspective, and the geomorphology of the Vajont Slide and the Vajont Valley has been neglected in all but a few papers. Nonetheless, geomorphological features and processes provide valuable insights into the preconditions and movement of the landslide. This paper presents the first engineering geomorphological maps of pre- and post-slide topography and their interpretation. The maps show changes in slope morphology, which indicate boundaries of landforms, and relationships between these landforms. Our interpretations support previous hypotheses, such as the existence of an ancient landslide in the same location as the 1963 event and the intact nature of the sliding mass. In addition, the landslide is proposed to have moved in two main blocks, with a possible third block on the west margin of the slide. A classification of failure scar morphology illustrates the implications of geomorphological features for failure behaviour, and the interaction between tectonic and geomorphic processes to precondition and degrade the slope to the point of failure is highlighted."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The 1963 Vajont Slide is one of the most studied natural disasters in the world, with over 150 publications on its cause, mechanisms, behaviour, and effects. Most of these studies have considered the event from a descriptive, engineering geology, structural geology, or geophysical perspective, and the geomorphology of the Vajont Slide and the Vajont Valley has been neglected in all but a few papers. Nonetheless, geomorphological features and processes provide valuable insights into the preconditions and movement of the landslide. This paper presents the first engineering geomorphological maps of pre- and post-slide topography and their interpretation. The maps show changes in slope morphology, which indicate boundaries of landforms, and relationships between these landforms. Our interpretations support previous hypotheses, such as the existence of an ancient landslide in the same location as the 1963 event and the intact nature of the sliding mass. In addition, the landslide is proposed to have moved in two main blocks, with a possible third block on the west margin of the slide. A classification of failure scar morphology illustrates the implications of geomorphological features for failure behaviour, and the interaction between tectonic and geomorphic processes to precondition and degrade the slope to the point of failure is highlighted.